Molecularly imprinted electrochemical sensor for monitoring mercaptan sulfur in aviation biofuel - Falone, Max Fabrício [UNESP]; Buffon, Edervaldo [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Elsevier, 2022)
This work reports the development and application of a molecularly imprinted electrochemical sensor based on the electropolymerization of pyrrole film on glassy carbon electrode for monitoring mercaptan sulfur in aviation biofuel. To this end, butanethiol was used as a template molecule for the formation of imprinted cavities in the polypyrrole structure. The modified electrode was characterized by cyclic voltammetry, electrochemical impedance spectroscopy, scanning electron microscopy and energy dispersive X-ray spectroscopy. After the optimization of the experimental conditions, the sensor presented linear working ranges in the concentration range of 1.0 × 10−12 to 1.0 × 10−10 mol L−1. The values obtained for the amperometric sensitivity and the limits of detection and quantification of this device were 5.1 × 105 A L mol−1, 6.1 × 10−13 mol L−1, and 2.0 × 10−12 mol L−1, respectively. The proposed sensor showed excellent selectivity, remarkable repeatability and high stability for butanethiol detection. The proposed electroanalytical method was successfully applied in aviation biofuel sample where it exhibited recovery values between 98% and 107%, with relative standard deviation ranging from 1.1% to 4.1%. The results obtained show that the proposed sensor has good accuracy and can be successfully applied for monitoring mercaptan sulfur in aviation biofuel samples.
Keywords: Aviation biokerosene; Butanethiol; Electrochemical sensor; Molecularly imprinted polymer; Polypyrrole